P493 Determination of Chlamydia trachomatis organism load in men with Non-Gonococcal Urethritis (NGU). (14th July 2019) - Williams, James; Jordan, Stephen; Ermel, Aaron; Toh, Evelyn; Batteiger, Teresa; Batteiger, Byron; Nelson, David
Abstract : Background: The ability to quantify the organism load of Chlamydia trachomatis (CT) using a commercial assay could expand insights from epidemiological studies. This approach can be applied to routine diagnostic testing, and multiple specimen types. Approximate CT organism load was determined in urine from men with NGU, with and without co-infections, by comparing the results from each positive sample to a set of CT standards using the Abbott Real time m 2000 ( m 2000) platform. Methods: Urine specimens, collected from men participating in the Idiopathic Urethritis Men's Project (IUMP), were tested on the m 2000 for CT. Additional testing included Neisseria gonorrhoeae, Mycoplasma genitalium, Trichomonas vaginalis, and Ureaplasma urealyticum . Standards were prepared by diluting CT elementary bodies (EB) into the collection device at six concentrations. CT organism load was determined by comparing the instrument generated delta cycle (DC) value from each CT positive urine to the standard curve. Calculated means were compared by t-test (p<0.05). Results: Two hundred and six men were tested for CT and 83 (40.3%) were positive. The DC values for 81/83 (97.3%) CT positive samples fell within the range of the standard curve. The mean DC value was 12.15 (range 0.19–16.96) which equated to a mean CT organism load of 1.4×10 6 EB/ml urine (range 2.22×10 2 -9.97×10 6 ). There was no difference between the mean organism load in specimens from men who did and did not have co-infections with other STIs, 2.04×10 6 versus 1.38×10 6 EB/ml, (p≥0.05). Conclusion: CT load determination can be performed on urine specimens using the m 2000. This could facilitate straightforward load determination in settings where routine testing is performed. In men with NGU, the CT organism load is high and no difference in CT load was observed in men with CT mono-infections and men co-infected with CT and other STIs. Disclosure: No significant relationships.